Lietuvos siekiai atgauti lenkų užimtas žemes 1920 metų vasarą - Lesčius, Vytautas (Lietuvos istorijos studijos, 2004)
Complicated and hostile relations between Poland and Lithuania developed since the very beginning of the restored independence. The Polish ruling strata of society were unwilling to recognize independent Lithuania and resorted to diverse measures to subjugate her. Under the pretext of the fight against the Bolsheviks, the Poles occupied a vast territory of Lithuania by the beginning of the 1920 summer. A state of undeclared war arose between Lithuania and Poland. Due to the adverse military actions against the Bolsheviks, the Poles were forced to mitigate their policy with respect to Lithuania. On July 4th, 1920, reluctant as they were, the Poles recognized Lithuania de facto and, within a few days, they committed themselves to the allies to make over Vilnius and its region to Lithuania. Under the peace treaty of July 12th, 1920, concluded with Soviet Russia, Lithuania was recognized as an independent and sovereign state, and its borders were delineated. With the Poles in full retreat from Lithuania, a good opportunity presented itself for recovering the other lands which had been formerly occupied by the Poles. The Lithuanian troops started successful actions to fulfill this task and by the end of 1920 they had liberated nearly all the lands which by the peace treaty of July 4th of the same year had been defined as Lithuania’s territory. Unfortunately, this task was not brought to an end, for having defeated the Bolsheviks near Warsaw, the Poles renewed their intrusion into the southern territories of Lithuania.